Análise da viabilidade técnica e econômica de implantação de uma usina solar: estudo de caso - Vasconcelos, Ismael Rodrigues de (Universidade Federal Rural do Semi-Árido, 2020)
Photovoltaic solar energy is a clean energy captured by means of solar irradiation, that is, it is the conversion of energy from solar irradiation into electrical energy through the process known as the "photovoltaic effect". This process always happens when sunlight strikes a photovoltaiccell.In thisinteraction, thephotonspresent inthesolarradiationinteract withthe free electrons of the photovoltaic cell and they gain the ability to move in a certain direction. The movement of electrons in the cell, in turn, results in an electric current. The present work aims to analyze the technical and economic feasibility of implementing a solar plant. To that end, a comparison was made between the energy bills from September 2017 to September 2019 at UFERSA campus Angicos, showing the difference between before and after the implantation of the solar photovoltaic plant on the campus, all with the help of an interactive andwiththesolarirradiationindexoftheplace.
Monografia
Keywords: Energia solar fotovoltaica; Fontes renováveis; Geração de energia; Photovoltaic solar energy; Renewable sources; Power generation; ENGENHARIAS::ENGENHARIA CIVIL